Differences in cortical activation with live music compared to recorded music: an fNIRS study - Flaagan, Carly, author; LaGasse, A. Blythe, advisor; Knight, Andrew, advisor; Rojas, Donald, committee member; Davalos, Deana, committee member (Colorado State University. Libraries, 2020)
The purpose of this study was to compare and assess the neural activations during live music and recorded music engagement in neurotypical adults aged eighteen to sixty years old within a social context. The research questions sought to answer if cortical activations in areas of the brain involved with social interaction would be different in the live music conditions compared to the recorded music conditions and if blood oxygenation levels across the entire cortical surface would be different in any area across the four conditions. This study was a within-subjects quasi-experimental design where each of the 32 recruited participants were exposed to all four conditions while mirroring the CR (clinician-researcher) in a tapping task. The four conditions were: recorded sung, recorded spoken, live sung, and live spoken. Participants were exposed to the four conditions as well as a rest condition in pseudo-randomized order. Each participant underwent five trials of each condition using a block design. Cortical activation was measured using functional near-infrared spectroscopy (fNIRS). A total of 27 participants were included in the analyses. Imaging results revealed significant differences in inferred cortical activation during live stimuli compared to recorded stimuli, live music compared to recorded music, music stimuli compared to non-music stimuli, live music compared to all other conditions, and live spoken stimuli compared to recorded spoken stimuli in brain regions of interest and globally. Results support the possibility that live music may have a greater effect than recorded music in regions of the brain that process social responses. Future research could better illuminate the comparisons of neural activations between live and recorded auditory stimuli.
Keywords: cortical activation; live music compared to recorded music; social; fNIRS; cognitive neuroscience; music therapy